2019
DOI: 10.9734/ajarr/2019/v4i330112
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Rural Women in Income Generating Activities from Agricultural Model Farm Project

Abstract: This study was conducted mainly to have an understanding about the participation of rural women in Bangladesh in income generating activities initiated by Agricultural Model Farm (AMF) project of Sabalamby Unnayan Samity (SUS), a famous NGO in Bangladesh. This also explained the relationship between extent of women participation in income generating activities initiated by AMF project of SUS and their selected characteristic. Data were collected from a sample of 90 rural women from 12 selected SUS groups in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was concluded that a negative significant relationship between communication media exposure and the impact of climate change on lemon productivity. A study was conducted on the participation of rural women in income-generating activities on the agricultural farm and found that communication media exposure had no significant relationship with the extent of participation in activities (Haque, 2008).…”
Section: Relationship Between Selected Socio-economic Characteristics...mentioning
confidence: 99%
“…It was concluded that a negative significant relationship between communication media exposure and the impact of climate change on lemon productivity. A study was conducted on the participation of rural women in income-generating activities on the agricultural farm and found that communication media exposure had no significant relationship with the extent of participation in activities (Haque, 2008).…”
Section: Relationship Between Selected Socio-economic Characteristics...mentioning
confidence: 99%